"Also and Above All a Regime of Justice". Criminal Law and the Aesthetics of Justice Under the Italian Fascist Regime: the role of architecture and the visual arts (Ágora Journal, 2025)
The article analyzes the relationship between criminal justice, architecture, and visual arts under the Italian fascist regime, highlighting their role in both repression and social consensus building. The objective is to investigate how fascism redefined justice, not only as a repressive tool but as a fundamental element of the "new State." Using an interdisciplinary approach, the research examines legal documents, political speeches, and visual representations, such as the Milan Palace of Justice and its artworks. The conclusion emphasizes that justice under fascism was not only repressive but also central to legitimizing the regime, using visual symbols to strengthen its ideology and consolidate state authority.
Keywords: Justice; Fascism; Architecture; Visual Artes